2019
DOI: 10.1051/0004-6361/201834479
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron lines in highly magnetized neutron stars

Abstract: Cyclotron lines, also called cyclotron resonant scattering features (CRSF) are spectral features, generally appearing in absorption, in the X-ray spectra of objects containing highly magnetized neutron stars, allowing the direct measurement of the magnetic field strength in these objects. Cyclotron features are thought to be due to resonant scattering of photons by electrons in the strong magnetic fields. The main content of this contribution focusses on electron cyclotron lines as found in accreting X-ray bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
221
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(247 citation statements)
references
References 394 publications
12
221
4
Order By: Relevance
“…Walter et al 2015). Typical magnetic field strength at the NS surface in XRPs is 10 12 G, which is confirmed independently by a number of different methods: detection of cyclotron lines (see Staubert et al 2019 for review), transitions into the "propeller" state (Tsygankov et al 2016;Lutovinov et al 2017), detection of spin-up and spin-down effects (Sugizaki et al 2017). Detected luminosities of XRPs cover a few orders of magnitude from 10 33 erg s −1 and up to 10 41 erg s −1 , where the brightest pulsars belong to the recently discovered class of pulsating ultraluminous X-ray sources (ULXs, Bachetti et al, 2014;Israel et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…Walter et al 2015). Typical magnetic field strength at the NS surface in XRPs is 10 12 G, which is confirmed independently by a number of different methods: detection of cyclotron lines (see Staubert et al 2019 for review), transitions into the "propeller" state (Tsygankov et al 2016;Lutovinov et al 2017), detection of spin-up and spin-down effects (Sugizaki et al 2017). Detected luminosities of XRPs cover a few orders of magnitude from 10 33 erg s −1 and up to 10 41 erg s −1 , where the brightest pulsars belong to the recently discovered class of pulsating ultraluminous X-ray sources (ULXs, Bachetti et al, 2014;Israel et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…Recently, D' Aì et al (2015) found a cyclotron absorption line at 4.7 keV in the spectrum obtained with EPIC/pn instrument on board of XMM-Newton, indicating the surface magnetic field strength of B = (5.27 ± 0.06) × 10 11 G. The same feature was independently discovered by Doroshenko et al (2015) in the older BeppoSAX data. Thus GRO J1744−28 has a magnetic field of intermediate strength when compared to other accreting magnetized NSs (see a review by Staubert et al 2019). This, together with the observed super-Eddington outbursts, implies that the magnetospheric radius and thus the inner radius of the accretion disk should be rather small, around 5×10 7 cm, which makes the Bursting Pulsar a unique object to study, particularly, in the context of super-Eddington accretion onto a NS as a mechanism to power ultraluminous X-ray sources.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Fürst et al (2018) interpret the two features as being fundamentals from distinct regions, in which case they possess higher fields, namely ∼ 3 × 10 12 G and ∼ 4.3 × 10 12 G (for z = 0), corresponding to cyclotron absorption radii differing by only around 12%. These fields are substantially above the values inferred from accretion torque models (see Table 1 of Staubert et al 2019), the converse of what is usually obtained when comparing these two field estimates for X-ray binary pulsars. Some CRSFs are observed to depend on pulse phase, time, and luminosity (Staubert et al 2019, and references therein).…”
Section: Introductionmentioning
confidence: 44%
“…These fields are substantially above the values inferred from accretion torque models (see Table 1 of Staubert et al 2019), the converse of what is usually obtained when comparing these two field estimates for X-ray binary pulsars. Some CRSFs are observed to depend on pulse phase, time, and luminosity (Staubert et al 2019, and references therein). These variations are sometimes attributed to a movement of the radiative shock along the accretion column, or by changes in the magnetic field geometry (e.g.…”
Section: Introductionmentioning
confidence: 44%